Analytical study of the reality of the application of administrative automation in sports clubs - Ali Rabeeah , Israa Jumaah; Malih, Fatimah Abed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary objective of this study was to identify the obstacles and problems encountered in the work of sports clubs according to the reality of the application of administrative automation. The present study was conducted in the sports club headquarters of Baghdad within the timeframe of October 2021 to December 2021. In the present study, a descriptive approach was used by the researchers in an analytical style according to the nature of the problem to be studied. The research community of the current study was composed of 100 sports clubs in the governorate of Baghdad. A total of 80 questionnaires were filled by the sample participants, who represented a percentage of 80% of the research community. After processing the results statistically using the SPSS software, the researchers concluded that sports clubs encounter a lot of difficulties regarding delay in implementing automation procedures in their administrative work, due to lack of financial allocations and lack of awareness among club workers regarding automation techniques.